Schools and religions: the law and the courts – Costa Rica, England, France, Italy, Senegal, South Africa, Switzerland and Turkey - Fancourt, N (Bloomsbury Academic, 2023)
The place of religions within schooling is almost inevitably bound up in various legal requirements, both national, often in constitutional arrangements, and supranational, such as human rights obligations. At a national level, constitutions can vary across a spectrum, from complete theocracy, such as contemporary Iran, to aggressive anti-religious atheism, notably in Communist states, such as the former Soviet Union or Maoist China. In between, there are more moderated forms of secularity, such as the paradigmatic case of laïcité in France, to an established religion, such as Greece. These positions are however not static, and countries adjust either constitutionally or simply administratively to political and social changes. One example has been the shift in post-Soviet states, such as Poland or Russia, towards greater recognition of religions. Other states have had to adjust to a decline in national religiosity, and/or to increasing religious diversity: Great Britain exemplifies both. However, in many states, constitutional changes are somewhat tectonic, requiring considerable explicit political energy and agreement to be approved, and instead, there are often new legal requirements that cover particular domains of public life, of which education is one. These are themselves sometimes in response to the organic changesin practice which schools and teachers make, and which governments then seek to make legally compulsory in all schools – or indeed to prohibit if they disapprove of them....